The Effect of Company Profitability and Company Size on Audit Report Lag Islamic Finance Companies Listed in Indonesia Stock Exchange - Ermi Herawati (International Journal of Sharia Business Management, 2022)
This study aims to evaluate and determine the effect of Profitability and Company Size on Audit Report Lag in Islamic Financial Companies listed on the Indonesia Stock Exchange from 2016 to 2020. This study uses secondary data and uses purposive samoling with predetermined criteria. The sample of this study uses 13 companies engaged in the Islamic Financial Institutional sub sector that have been listed on the Indonesia Stock Exchange for the period 2016 to 2020. The analytical technique used in this study uses multiple linear regression analysis and uses the Eviews version 9 application. The results of this study indicate that Profitability and Company Size have a significant and simultaneous effect on Audit Report Lag. With a coefficient of determination of 0.870044, this states that the independent variable explains the dependent variable 87%. And the remaining 13% id influenced by other independent variables outside of this study